(untitled) (Research, Society and Development, 2023)
This study aims to conduct a narrative review of the literature to understand the causal relationship between acute kidney disease and Covid-19 and to point out new updates on the subject. The world has been impacted by the coronavirus disease 2019 pandemic, a severe acute respiratory syndrome caused by the SARS-CoV-2 coronavirus, with kidney conditions as one of the most frequent pathological consequences. Acute kidney injury is a condition that the concentrations of urea and creatinine in the blood increase through the retention of nitrogenous wastes, decrease the glomerular filtration rate, as well as the volume of extracellular fluid causing a derangement of body electrolyte homeostasis. Injuries to the renal system related to viral infection can occur due to: direct damage to epithelial cells and the renal vascular endothelium, and the indirect ones due to the disorganization between the balance of the renin-angiotensin system, activation of coagulation pathways, activation of inflammatory pathways and hypoxemia. To date, epidemiological studies indicate that a high condition of association between Covid-19 and kidney diseases. The harmful relationship between SARS-CoV-2 infection and acute kidney diseases is notorious, but new searches are crucial to better understand its etiology.